Penataran Pemanfaatan Wondershare Sebagai Media Pembelajaran Bagi Guru di SMPN 1 Sungai Penuh - Pujaningsih, Febri Berthalita; Amnie, Erlida; Pathoni, Haerul; Astalini, Astalini; Susanti, Nova (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Limited face-to-face learning requires teachers to have alternative solutions in packaging the delivery of learning materials more interestingly and not making students feel bored. Teachers have difficulty in creating learning media that is suitable for students so that students who take part in learning activities are less enthusiastic. Efforts that can be made to overcome this problem can be done by upgrading the use of wondershare as an attractive, effective, and efficient learning medium. The purpose of this upgrading activity is to maximize the quality of learning in the classroom. The upgrading participants were science teachers in Sungaipuh and the place where the community service was held at SMP Negeri 1 Sungaipuh, Kerinci. After participating in upgrading activities, teachers can innovate in developing alternative learning media by making attractive learning videos. The positive effect of this activity is that learning can be carried out in a more interesting and less boring way.